Neuromorphic computing systems for industry 4.0 - Dhanasekar, Subramaniyam 1983-; Sagayam, K. Martin 1987-; Vijh, Surbhi 1993-; Tyagi, Vipin; Norta, Alex 1972- (IGI Global, 2023)
"The comprehensive and timely publication aims to be an essential reference source, on the available literature in the field of Neural computing-based Microchip Technology. This will provide further research opportunities in these dynamic fields. It is hoped that this handbook will provide the resources necessary for researchers, advanced level students, technology developers to adopt and implement the advances in technology and applications"--
Keywords: Neuromorphics; Neural computers; Artificial intelligence; Industry 4.0